2008
DOI: 10.1097/mao.0b013e31817f736b
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Diagnostic Criteria for Acute Mastoiditis in Children

Abstract: Acute mastoiditis in children is an entity that is poorly evaluated and understood in the modern literature. There is a lack of consensus regarding the criteria and strategies for diagnosing acute mastoiditis in the pediatric population. It is crucial that such criteria are established, and consensus is achieved so that prognostic and controlled studies can be initiated to identify risk factors and establish the most effective management of this condition in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 62 publications
3
60
1
3
Order By: Relevance
“…The most frequently used laboratory test was white blood count (100% of patients in 45 of 65 studies). In 63 studies, the result of culturing from the otomastoid was reported with Streptococcus pneumoniae the most frequently isolated bacterium [8]. The microbiology of AOM has changed in the heptavalent pneumococcal conjugate vaccine (PCV) era.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used laboratory test was white blood count (100% of patients in 45 of 65 studies). In 63 studies, the result of culturing from the otomastoid was reported with Streptococcus pneumoniae the most frequently isolated bacterium [8]. The microbiology of AOM has changed in the heptavalent pneumococcal conjugate vaccine (PCV) era.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with concurrent cholesteatoma or previous surgery for cholesteatoma were also excluded ( Fig. 1), since cholesteatoma is considered a specific condition and is therefore not usually included in AM studies in children [4]. The study was approved by the Regional Ethical Review Board in Lund (H4 143/2007).…”
Section: Methodsmentioning
confidence: 99%
“…There is lack of consensus on current diagnostic criteria. 10,12 Published data from Taiwan on mastoiditis in children have been limited to two retrospective reports involving a total of 38 patients over the past decade. 7,8 Our retrospective study on 104 children with mastoiditis offers a unique opportunity to re-examine the clinical spectrum and diagnostic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a recent systemic review of diagnostic criteria for acute mastoiditis in children, it was suggested that this disease is poorly evaluated and understood and there is lack of consensus regarding the criteria and strategies for diagnosing acute mastoiditis in the pediatric population. 10 To date only scanty clinical and microbiological data on mastoiditis in children are available in Taiwan. Two reports on mastoiditis in Taiwanese children have been published over the past decade.…”
Section: Introductionmentioning
confidence: 99%